PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA KARYAWAN PT. ASURANSI JIWASRAYA MALANG - Matheous Tamonsang (Gapenas Publisher, 2021)
PT. Asuransi Jiwasraya Malang seeks to improve services to its customers through improving the performance of its employees, one of which is by increasing the emotional intelligence and spiritual intelligence of its employees. Therefore, this study aims to examine how far the influence of the level of emotional intelligence and spiritual intelligence affects the performance of employees of PT. Asuransi Jiwasraya Malang. This study uses the entire population as many as 57 employees of PT. Asuransi Jiwasraya Malang as respondents. Data was collected using a questionnaire that was distributed and then processed using a Likert scale. By using the multiple linear regression method, the results obtained that emotional intelligence (X1) and spiritual intelligence (X2) affect the performance of employees of PT. Asuransi Jiwasraya Malang. On the other hand, the variable that has the dominant influence on employee performance is emotional intelligence (X1).